Female gender and Helicobacter pylori infection, the most important predisposition factors in a cohort of gastric cancer: A longitudinal study - Shahram Agah; Hossein Khedmat; Mohammad Ebrahim Ghamar-Chehred; Reza Hadi; Aghdas Aghaei (Babol University of Medical Sciences, 2016)
Background: Gastric cancer (GC) is one of the most common Cancers in the world and Helicobacter pylori (HP) infection is considered a causative factor. The aim of this study was to determine the characteristics and the associated factors of (GC) in a small cohort. Methods: Overall, 54 patients with diagnosed gastric cancer were followed-up at the Department of Gastroenterology & Hepatology at Baqiyatallah University of Medical Sciences. 37 (68.5%) of them were positive for H pylori infection in histopathological evaluations. Univariate and multivariate regression analyses were used to determine the associations of demographic features and HP infection status with GC characteristics and prognosis. Results: Univariate analysis showed female gender (odds ratio (OR): 6.53; 95% confidence interval (95%CI): 1.59-26.8; P=0.008), and illiteracy (compared to intermediate education; OR: 5.9, 95%CI: 1.37-25.43; p=0.05) were associated significantly with higher rate of HP infection. After a mean±SD follow-up duration of 254±329 months, only female gender was significantly associated with HP infection in GC (OR:4.56; 95% CI: 1.0-21.76; P=0.05). H pylori positive patients had significantly higher grade of GC (OR: 3.97; 95% CI: 1.0-16.16; P=0.05), and a trend toward greater GC stage (OR: 4.46, 95% CI: 9.39-21.23; p=0.06). There was no association between survival rate and H pylori infection. Conclusion: In the current study, we found a significant association of female gender with GN and an association of higher grade of GC with female gender. These findings may indicate a sex disparity in susceptibility to HP infection regarding GC future studies of larger populations are recommended.